2017
DOI: 10.1080/14658011.2017.1280642
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and MesoDyn simulations for the miscibility of polyvinyl alcohol/polyvinyl pyrrolidone blends

Abstract: The miscibility of polyvinyl alcohol (PVA)/polyvinyl pyrrolidone (PVP) blends is investigated by atomistic molecular dynamics (MD). Specific volumes of five PVA/PVP blends (with mass ratio (ω, ω = m PVA /m PVP ) at 25%, 50%, 100%, 200% and 400%) as well as pure PVA and PVP are reviewed at the temperature of 298 K. The Flory-Huggins parameter x determined from the cohesive energy densities and the radial distribution functions of the inter-molecular atoms suggest that PVA/PVP blends can be miscible at all sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The formation of H-bonds between the acceptor and donor species can drive mixing of the polymer(s) and/or mixing between polymers and small molecules/additives. There are many studies that show the effects of competition between intra- and interchain H-bonding, accessibility of the donor and acceptor groups, steric crowding, and spacing between donor and acceptor groups on the mixing/demixing within the blends. For example, it has been shown that interchain contacts can be favored via optimal placement and separation of the H-bonding donor and acceptor groups along each polymer. , The increasing flexibility of the polymer chain can drive more intrachain H-bonds over interchain H-bonds, leading to demixing of the blend components . In polymer–nanoparticle blends, one can direct the dispersion/assembly of H-bond acceptor decorated particle surfaces in a matrix comprised of H-bond donor containing polymer chains (e.g., see Figure b and refs ) Studies have shown that incorporating directional interactions like H-bonds can also program stimuli-responsive structural changes into the macromolecular material.…”
mentioning
confidence: 99%
“…The formation of H-bonds between the acceptor and donor species can drive mixing of the polymer(s) and/or mixing between polymers and small molecules/additives. There are many studies that show the effects of competition between intra- and interchain H-bonding, accessibility of the donor and acceptor groups, steric crowding, and spacing between donor and acceptor groups on the mixing/demixing within the blends. For example, it has been shown that interchain contacts can be favored via optimal placement and separation of the H-bonding donor and acceptor groups along each polymer. , The increasing flexibility of the polymer chain can drive more intrachain H-bonds over interchain H-bonds, leading to demixing of the blend components . In polymer–nanoparticle blends, one can direct the dispersion/assembly of H-bond acceptor decorated particle surfaces in a matrix comprised of H-bond donor containing polymer chains (e.g., see Figure b and refs ) Studies have shown that incorporating directional interactions like H-bonds can also program stimuli-responsive structural changes into the macromolecular material.…”
mentioning
confidence: 99%
“…The intermolecular distribution functions have been used to ascertain the degree of miscibility of component blends. Some researchers have proposed that, when heterocontacts between the two components in a blend reach higher g ( r ) values than contacts between the same component, miscibility occurs, whereas when this is not the case, the system phase separates. Analysis of RDFs, shown in Figures , and , revealed a distinct peak at 5–6 Å. For quercetin (Figure ), the peak maxima of B1–MB and B2–MB is lower than that found for the pure components (B1–B1 and B2–B2), which indicates that B1–MB and B2–MB bead pairs are immiscible, unlike B1–ACN and B2–ACN beads pairs, which are miscible.…”
Section: Resultsmentioning
confidence: 95%
“…The results revealed that, due to the involvement of hydrogen and the van der Waals bond between the elements, the constituent polymers exhibited good compatibility at all compositions. The blend of PVA and PVP is chosen as the host material in this study because of its improved stability due to inter-chain hydrogen bonding between carbonyl group of PVP and the OH group of PVA; a weak physical cross-linking exists in the blend material due to this hydrogen bonding [24][25][26][27][28]. Simulation was also employed by researchers in order to study the miscibility of PVA-PVP blend with various mixing ratios, from 25% up to 400% [24].…”
Section: Introductionmentioning
confidence: 99%
“…The blend of PVA and PVP is chosen as the host material in this study because of its improved stability due to inter-chain hydrogen bonding between carbonyl group of PVP and the OH group of PVA; a weak physical cross-linking exists in the blend material due to this hydrogen bonding [24][25][26][27][28]. Simulation was also employed by researchers in order to study the miscibility of PVA-PVP blend with various mixing ratios, from 25% up to 400% [24]. Simulation study as well as experimental investigations also provides support for the miscibility of PVA-PVP blend in all compositions [24,26].…”
Section: Introductionmentioning
confidence: 99%